PENANAMAN NILAI KETELADANAN MELALUI PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM MASA KANAK-KANAK NABI MUHAMMAD SAW PADA SISWA KELAS III MI LENGKONGRASA - Euis Siti Aisyah; Nailannaza Nur Avipah; Aulia Zahra Rahmani; Septian Argiansyah (Jurnal Cahaya Edukasi, 2026)
This study aims to describe the implementation of Islamic Cultural History (SKI) learning on the topic of the Childhood of Prophet Muhammad SAW and its role in instilling exemplary values among third-grade students at MI Lengkongrasa. This research employed a qualitative descriptive approach. Data were collected through observation, interviews, and documentation. The results showed that the learning process was carried out through preliminary, core, and closing activities systematically. The teacher applied lecture and question-answer methods to deliver the material and relate it to students' daily lives. The exemplary values instilled included honesty, responsibility, discipline, politeness, trustworthiness, and social care. The interaction between teachers and students was well established, supporting the achievement of learning objectives. The obstacles encountered were students' lack of focus and limited learning media. To overcome these challenges, the teacher provided motivation, applied interactive questioning techniques, and connected the material to real-life experiences. Therefore, SKI learning on the Childhood of Prophet Muhammad SAW contributes significantly to character building among elementary-level students.